2008 labour overview : Latin America and the Caribbean. (Labour overview : Latin America and the Caribbean, 2009)
Annotation The 2008 Labour Overview for Latin America And The Caribbean is special. This edition provides evidence of the effects of an unprecedented international crisis that has cast a shadow over the global economy and is reflected in the employment situation in the region. Employment will be a challenge in 2009. As ILO Director-General, Juan Somavia stated, "The ILO's message is realistic, not alarmist" with respect to this situation. it should be stressed that this crisis is not hitting the region at a bad time. The region has experienced several years of favourable economic growth, which has had a direct impact on the employment situation. The 2008 Labour Overview indicates that unemployment diminished For The fifth consecutive year, permitting Latin America And The Caribbean to reach unemployment rates not seen since 1992. The 2008 Labour Overview states that these results mark the end of a positive cycle in the urban unemployment rate. According To The figures for urban employment provided by the countries, which our specialists used to conduct the analysis, The effects of the economic slowdown became apparent beginning in the third quarter of 2008.